The Influence of Work Motivation, Leadership Style, and Organizational Citizenship Behavior on Nurses' Turnover Intention at Mitra Jambi Hospital - Febrian Tan Jaya; Rokiah Kusumapradja; Intan Silviana Mustikawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background: Nurse turnover intention is a significant problem for hospitals, including RS Mitra Jambi, as it can affect operational stability and the quality of healthcare services. A decrease in the number of experienced nurses can negatively impact the effectiveness of hospital services. Therefore, it is important to understand the factors influencing turnover intention, such as work motivation, leadership style, and Organizational Citizenship Behavior (OCB) culture. Objective: This study aimed to analyze the effect of work motivation, leadership style, and OCB culture on nurse turnover intention at RS Mitra Jambi. Methods: This research uses a quantitative method with a survey approach. Data were collected through questionnaires distributed to nurses at RS Mitra Jambi. Data analysis was conducted using multiple linear regression to test the relationships between independent variables (work motivation, leadership style, OCB culture) and the dependent variable (turnover intention). Results: Work motivation, leadership style, and OCB culture simultaneously have a significant effect on turnover intention (p<0.05). Work motivation, leadership style, and a positive OCB culture have a significant negative effect on turnover intention (p<0.05). Conclusion: Work motivation, transformational leadership style, and OCB culture significantly influence nurse turnover intention at RS Mitra Jambi. The results of this study provide guidance for hospital management to develop strategies for enhancing work motivation, implementing transformational leadership styles, and strengthening OCB culture to improve nurse retention.